Pengaruh Pariwisata Pendakian Gunung Prau Terhadap Ekonomi Masyarakat Desa Patak Banteng Kabupaten Wonosobo - Ryan Muhammad Daris; Holi Bina Wijaya (Teknik PWK (Perencanaan Wilayah Kota), 2017)
Patak Banteng is a village at the tracking path to reach the summit of Mount Prau, which visitors has increase. The development of tourism at the village has impact in the economic sector. This research focuses on the influence of tourism on the economy of Patak Banteng Village. The research approach uses a descriptive quantitative to determine the characteristics of existing and also the influence of the tourism on the economy itself.          The research result shows that there is impact of tourism to the local economy in Patak Banteng Village. The existence of these tourist activities accommodate 13 people who previously did not have job and involves 8% of citizens in productive age. From 120 respondents, mostly they have additional income after working in tourism sector, in this case shows one of the positive impacts from tourism activities is increasing resident’s income. One of the adverse effects of tourism itself is dependence, and at the village of Patak Banteng, dependence figure is 43 out of the total respondents and the majority come from tourist manager. Dependence on this tourism can be bad when it comes the time the tourism is closed.